Metal Chalcogenide Thin Films for Photoelectrochemical Cell Applications: A Review - Ho, Soon Min (IDOSI Publications, 2016)
Metal chalcogenide thin films represent an important family of semiconductor materials in photoelectrochemical cell. Binary and ternary thin films hold promise in photoelectrochemical cell applications such as they are efficient absorbers in the visible and near infrared regions of solar spectrum. In this work, the fabrication of photoelectrochemical cell by using various types of thin films as photoelectrode will be discussed. Then, the conversion efficiency and fill factor of obtained films will be investigated.